The Australian longitudinal study on male health-methods. (October 2016) - Currier, Dianne; Pirkis, Jane; Carlin, John; Degenhardt, Louisa; Dharmage, Shyamali; Giles-Corti, Billie; Gordon, Ian; Gurrin, Lyle; Hocking, Jane; Kavanagh, Anne; Keogh, Louise; Koelmeyer, Rachel; et al.
Abstract Background The Australian Longitudinal Study on Male Health (Ten to Men) was established in 2011 to build the evidence base on male health to inform policy and program development. Methods Ten to Men is a national longitudinal study with a stratified multi-stage cluster random sample design and oversampling in rural and regional areas. Household recruitment was conducted from October 2013 to July 2014. Males who were aged 10 to 55 years residing in private dwellings were eligible to participate. Data were collected via self-completion paper questionnaires (participants aged 15 to 55) and by computer-assisted personal interview (boys aged 10 to 14). Household and proxy health data for boys were collected from a parent via a self-completion paper-based questionnaire. Questions covered socio-demographics, health status, mental health and wellbeing, health behaviours, social determinants, and health knowledge and service use. Results A cohort of 15, 988 males aged between 10 and 55 years was recruited representing a response fraction of 35 %. Conclusion Ten to Men is a unique resource for investigating male health and wellbeing. Wave 1 data are available for approved research projects.